Trimodality therapy for esophageal cancer: The role of surgical and radiation treatment parameters in the development of anastomotic complications. Issue 23 (15th October 2021) - Alfaifi, Salem; Chu, Robert; Hui, Xuan; Broderick, Stephen; Hooker, Craig; Brock, Malcolm; Bush, Errol; Hales, Russell; Anderson, Lori; Hoff, Jeffrey; Friedes, Cole; Han‐Oh, Sarah; et al.
Abstract: Background: Here, we investigated the relationship between clinical parameters, including the site of surgical anastomosis and radiation dose to the anastomotic region, and anastomotic complications in esophageal cancer patients treated with trimodality therapy. Methods: Between 2007 and 2016, esophageal cancer patients treated with trimodality therapy at a tertiary academic cancer center were identified. Patient, treatment, and outcome parameters were collected. Radiation dose to the gastric regions were extracted. Anastomotic complication was defined as leak and/or stricture. We used Fisher's exact and Wilcoxon rank‐sum tests to compare the association between clinical parameters and anastomotic complications. Results: Of 89 patients identified, the median age was 63 years, 82% ( n  = 73) were male, and 82% had distal ( n  = 47) or gastroesophageal junction ( n  = 26) tumors. Median follow‐up was 25.8 months. Esophagectomies were performed with cervical (65%, n  = 58) or thoracic anastomoses (35%, n  = 31). Anastomotic complications developed in 60% ( n  = 53). Cervical anastomosis was associated with anastomotic complications (83%, n  = 44/53, p  < 0.01). Radiation to any gastric substructure was not associated with anastomotic complications ( p  > 0.05). In the subset of patients with distal/gastroesophageal junction tumors undergoing esophagectomy with cervical anastomosis where radiation was delivered to the future neoesophagus, 80% ( n  = 35/44) developed anastomotic complications. In this high‐risk subgroup, radiation was not associated with anastomotic complications ( p  > 0.05). Conclusions: Our analysis did not demonstrate an association between radiation dose to gastric substructures and anastomotic complications. However, it showed an association between esophagectomy with cervical anastomosis and anastomotic complications. Patients with distal/gastroesophageal junction tumors who undergo esophagectomy with cervical anastomosis have higher rates of anastomotic complications unrelated to radiation to gastric substructures. Abstract : In trimodality therapy for esophageal cancer, radiation dose to any individual gastric substructure was not associated with anastomotic complications but anastomotic location (cervical vs. thoracic) is more closely associated with whether patients will experience anastomotic complications than neoadjuvant radiation treatment parameters. These data support the safety of neoadjuvant chemoradiation prior to esophagectomy for patients with esophageal cancers.